Emerging role of antidiabetic drugs in cardiorenal protection - Fu, Wen-Jia; Huo, Jin-Ling; Mao, Zi-Hui; Pan, Shao-Kang; Liu, Dong-Wei; Liu, Zhang-Suo; Wu, Peng; Gao, Zhong-Xiuzi (Frontiers in Pharmacology, 2024)
The global prevalence of diabetes mellitus (DM) has led to widespread multi-system damage, especially in cardiovascular and renal functions, heightening morbidity and mortality. Emerging antidiabetic drugs sodium-glucose cotransporter 2 inhibitors (SGLT2i), glucagon-like peptide-1 receptor agonists (GLP-1RAs), and dipeptidyl peptidase-4 inhibitors (DPP-4i) have demonstrated efficacy in preserving cardiac and renal function, both in type 2 diabetic and non-diabetic individuals. To understand the exact impact of these drugs on cardiorenal protection and underlying mechanisms, we conducted a comprehensive review of recent large-scale clinical trials and basic research focusing on SGLT2i, GLP-1RAs, and DPP-4i. Accumulating evidence highlights the diverse mechanisms including glucose-dependent and independent pathways, and revealing their potential cardiorenal protection in diabetic and non-diabetic cardiorenal disease. This review provides critical insights into the cardiorenal protective effects of SGLT2i, GLP-1RAs, and DPP-4i and underscores the importance of these medications in mitigating the progression of cardiovascular and renal complications, and their broader clinical implications beyond glycemic management.